ACE I/D polymorphism and cardiac adaptations in adolescent athletes - Rizzo, M.; Gensini, F.; Fatini, C.; Manetti, P.; Pucci, N.; Capalbo, A.; Vono, M. C.; Galanti, G. (Medicine & Science in Sports & Exercise, 2003)
PURPOSE: The aim of this cross-sectional study was to determine whether there is a correlation between left ventricular hypertrophy (LVH) and angiotensin converting enzyme (ACE) insertion/deletion (I/D) polymorphism in adolescent athletes. METHODS: Seventy-five competitive soccer players (aged 15 +/- 1.2 yr) and 52 untrained control subjects (aged 15 +/- 1.6 yr) were examined with echocardiography (echo) and bioelectrical impedance analysis. The ACE genotype of all subjects was determined by PCR and correlated with left ventricular mass (LVM) indices. RESULTS: Allele frequencies were comparable between athletes and controls. Body surface area (BSA), fat-free mass (FFM), and all mean echo measurements were significantly greater in athletes than in controls. LVM and LVM indices for both BSA and FFM were all significantly greater in athletes than in controls (LVM 195.3 +/- 32 g vs 165.3 +/- 37.6 g; LVM/BSA 115.5 +/- 18.9 g x mq(-1) vs 95 +/- 18.2 g x mq(-1); LVM/FFM 3.5 +/- 0.5 vs 3 +/- 0.54, P < 0.001 for the three variables). Left ventricular hypertrophy was found in 17 (23%) athletes. There was no correlation between ACE I/D polymorphism and athletes with LVH as the II and DD genotype frequencies were identical (41%). However, in athletes with LVH, the presence of the D allele was associated with a greater LVM index than compared to homozygous II genotype (LVM = 145 +/- 7.6 g x mq(-1) in DD+ID group vs 135 +/- 2.9 g x mq(-1) in II group, P = 0.008). CONCLUSIONS: The results of the study show that significant changes occur in cardiac morphology and function in adolescent athletes. Interestingly, the ACE I/D polymorphism was associated with the degree of cardiac hypertrophy but not with the occurrence of LVH itself.